Neural signatures of heterogeneity in risk‐taking and strategic consistency. (12th October 2021) - Leota, Josh; Kleinert, Tobias; Tran, Alex; Nash, Kyle
Abstract: People display a high degree of heterogeneity in risk‐taking behaviour, but this heterogeneity remains poorly understood. Here, we use a neural trait approach to examine if task‐independent, brain‐based differences can help uncover the sources of heterogeneity in risky decision‐making. We extend prior research in two key ways. First, we disentangled risk‐taking and strategic consistency using novel measures afforded by the Balloon Analogue Risk Task. Second, we applied a personality neuroscience framework to explore why personality traits are typically only weakly related to risk‐taking behaviour. We regressed participants' ( N  = 104) source localized resting‐state electroencephalographic activity on risk‐taking and strategic consistency. Results revealed that higher levels of resting‐state delta‐band current density (reflecting reduced cortical activation) in the left dorsal anterior cingulate cortex and the left dorsolateral prefrontal cortex were associated with increased risk‐taking and decreased strategic consistency, respectively. These results suggest that heterogeneity in risk‐taking behaviour is associated with neural dispositions related to sensitivity to the risk of loss, whereas heterogeneity in strategic consistency is associated with neural dispositions related to strategic decision‐making. Finally, extraversion, neuroticism, openness, and self‐control were broadly associated with both of the identified neural traits, which in turn mediated indirect associations between personality traits and behavioural measures. These results provide an explanation for the weak direct relationships between personality traits and risk‐taking behaviour, supporting a personality neuroscience framework of traits and decision‐making. Abstract : This study demonstrates that lower activation in the left dACC and the left DLPFC in the resting brain are associated with increased risk‐taking and decreased strategic consistency, respectively. Thus, heterogeneity in risk‐taking is associated with neural dispositions related to sensitivity to the risk of loss, and heterogeneity in strategic consistency is associated with neural dispositions related to strategic decision‐making. Both identified neural traits mediate indirect associations between personality traits and behaviour, supporting a personality neuroscience framework of traits and decision‐making.